Black wattle tannin as a zinc phosphating coating sealer. (4th November 2013) - Peres, Rafael Silveira; Cassel, Eduardo; Ferreira, Carlos Arthur; Azambuja, Denise Schermann
<x xml:space="preserve">Abstract</x> This paper reports an investigation into the use of condensed black wattle tannin as an environmental friendly sealer after zinc phosphating of carbon steel. In order to verify the sealer efficiency against corrosion, electrochemical impedance spectroscopy, potentiodynamic polarisation and salt spray tests were performed. To verify the pore modifications and phase compositions, SEM, electron dispersive spectroscopy and X‐ray diffraction analysis were carried out. The influence of the sealer on the adherence of finishing coatings was analysed. The results show that the tannin/sealer did not affect the final coating adhesion and improved the corrosion resistance of sealed samples. Copyright © 2013 John Wiley & Sons, Ltd.